A Trust Model for Detecting Device Attacks in Mobile Ad Hoc Ambient Home Network - Solomon, Akinboro; Olajubu, Emmanuel; Ogundoyin, Ibrahim; Aderounmu, Ganiyu (International Journal of Advanced Pervasive and Ubiquitous Computing, 2020)
International Journal of Advanced Pervasive and Ubiquitous Computing, Vol 2, p.17